Structural, optical and electrical properties of molecular hybrid films based on rare earth quinoline complexes (REQ3) chelated with bidentate ligands / Nor Khairiah Za'aba - Nor Khairiah, Za'aba (2012)
The molecular hybrid compound based on metal quinoline, Mq3 complexes were expected to give good electroluminescence and carrier transport properties. However, obtaining pure emission colour from the metal quinolinate complexes has always been a problem because most of the materials exhibit broad emission spectra with a full width at half maximum (FWHM) around 50-200 nm. The combined properties of rare earth as the metal centre and tris-(8-hydroxyquinolates) (8Hq) as the chelating ligand (centre ligand) as well as the adduction of the bidentate ligand which are 1,10-phenanthroline (Phen) and 2,2- bipyridine (Bpy) as the secondary ligand make these rare earth quinoline (Req3) ternary complexes ideal for use in optoelectronic devices. In this work, four different Req3 ternary complexes namely, Euq3bpy3, Euq3phen3, Tbq3bpy3 and Tbq3phen3 were synthesized and coated as thin films by spin coating technique. The FTIR and XRD measurements were performed in order to study the spectroscopic and structural nature of the film. The thermal properties were evaluated from TGA/DTG analysis. The UV-Vis and PL measurement were also carried out. UV-Vis absorption results reveal that the absorption process of the Req3 complexes are dominated by the neutral ligand (secondary ligand) indicating that chelated ligand has overcome the limitation of an intrinsically absorption coefficient for the rare earth metals (Re3+) . It is also proven that the different degree in the green coloured fluorescence detected in the PL spectra is due to the fact that the energy transfer between the triplet state and the Re3+ is inefficient. The J-V characteristics of Req3 ternary complexes film are also investigated. The Richardson-Schottky thermionic emission is found to dominate the transport mechanism. The electronics parameters of the ITO/Req3 ternary complexes/Al are also extracted from the conventional ln J- V and Cheung’s functions.